A Synthesis of Science Communication Practices in Auto Museums: Taking Beijing Auto Museum as an Example - Shi, Shuyang (International Theory and Practice in Humanities and Social Sciences, 2025)
As an important carrier of scientific and cultural communication, auto museums play a unique role in public science popularization. This paper takes Beijing Auto Museum as an example to review the practice of science communication in auto museums, and systematically sort out its mode of science communication practice through field research and case study analysis and other research methods. The study focuses on the four dimensions of exhibition communication, academic communication, public education, and cultural creativity, and reveals the innovative path of cross-border integration of contemporary auto museums. In terms of exhibition communication, it builds a dual narrative system of ‘science and technology + humanities’, and realizes the concrete expression of technical principles through immersive scenarios and interactive exhibits; in terms of academic communication, it relies on the publication of academic research and cooperation in academic exchanges to promote the production and transformation of knowledge; in terms of publicity and education, it develops science popularization activities, communication and publication, innovates the mode of science popularization education for young people by means of digitalization; in terms of cultural creativity, the development of ‘theatre + film + radio’ joint communication mechanism and cultural creativity venues has enabled the sustainable communication of science and culture. The study found that Beijing Auto Museum has successfully realized the transformation from collection display to value transmission by constructing a science communication system, and its communication paradigm provides operational experience for science and technology museums, which is of great significance in enhancing public scientific literacy and promoting science communication.